Primary antiphospholipid antibody syndrome presenting as acute superior mesenteric vein thrombosis - C., Vignesh N.; D., Manivannan; S., Maniselvi; R., Kannan (International Surgery Journal, 2021)
Antiphospholipid antibody syndrome (APS) is an autoantibody mediated thrombophilia characterised by recurrent arterial or venous thrombosis and/or pregnancy morbidity. APS presenting as thrombosis in mesenteric venous system is relatively uncommon (10%). Here, we present a case of primary APS presenting as acute superior mesenteric vein (SMV) thrombosis in a 38-year-old female. She was admitted with the complaints of abdominal pain and constipation for five days. Her abdomen was distended with sluggish bowel sounds. Her abdominal contrast enhanced computed tomography revealed thrombosis of SMV, splenic vein and portal vein. She was initially kept on conservative management and started on anticoagulants. Her coagulation work-up revealed that she was positive for anticardiolipin antibody and therefore, the diagnosis of APS was made. She was continued on conservative management and anticoagulants. On the tenth day of admission, after starting oral diet, she developed severe abdominal pain and abdominal signs of peritonitis. She was then taken up for emergency laparotomy. Intraoperatively; there was 100 cm of gangrenous ileal segment, about 60 cm from ileocecal junction and 160 cm from duodenojejunal flexure. The gangrenous ileal segment was resected and a double barrel ileostomy was constructed. She had an uneventful postoperative recovery and was started on lifelong anticoagulants.